ASTEC-Na code: Thermal-hydraulic model validation and benchmarking with other codes. (September 2018) - Bandini, G.; Ederli, S.; Perez-Martin, S.; Haselbauer, M.; Pfrang, W.; Herranz, L.E.; Berna, C.; Matuzas, V.; Flores y Flores, A.; Girault, N.; Laborde, L.
Highlights: ASTEC-Na sodium thermal-hydraulic models have been assessed in the JASMIN project. Experiments used: CABRI (3), SCARABEE (3), KNS-37 (1), KASOLA (7) and PHENIX (1). ASTEC-Na is benchmarked against CATHARE, RELAP5-Na, SIMMER-III and SAS-SFR. Conclusions on the ASTEC-Na sodium thermal-hydraulic models performance are presented. Abstract: This paper describes the work performed within the WP2.1 of the JASMIN project to validate the thermal-hydraulic models of ASTEC-Na code. The experiments used for validation purposes have been: BI1, E8 and EFM1, carried out in the CABRI reactor; BE + 3, APL1 and APL3, carried out in the SCARABEE reactor and N02, conducted in the KNS facility. ASTEC-Na has been also successfully applied (pretest calculations) to assess the performances of the KASOLA sodium loop and to verify its response under different operating conditions. Finally, a PHENIX natural circulation test has also been performed with ASTEC-Na. Besides, these experimental tests have been used as a code benchmarking exercise where thermal-hydraulic codes (CATHARE, RELAP5-Na and RELAP5-3D) and severe accident codes (SIMMER-III and SAS-SFR) have been compared with ASTEC-Na.